Application of a Four-Tier Diagnosis Test for Evaluating Student's Misconception about Blood Classification - Syarafina Syarafina; Zainul Mustofa (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
Background: A misconception is a form of error in scientific knowledge that is believed to be accurate. As a result, someone who has a misconception of something will reject scientific truth and will hinder the assimilation of new knowledge. The purpose of this study was to identify misconceptions that occur in students regarding the topic of blood classification. Methods: The survey method research was conducted on 97 students scattered in Malang and Tulungagung, Indonesia. The data analysis technique uses coding for categorization into four categories: conceptual understanding, partial understanding, misconception, and not understanding the concept. Results: The results showed that misconceptions occurred in all sub-topics of blood classification. Misconceptions were found in the concept of blood plasma (2.1%), white blood cells (6.2%), thrombocytes (17.5%), and blood classification system (8.2%). Misconceptions occur due to several misunderstandings of students such as red blood cells that play a role in transporting nutrients, haemoglobin only binds oxygen, and difficulty distinguishing between antigens and antibodies in determining blood groups, blood donation, and the impact arising from donations. Conclusion: The existence of misconceptions causes students' mastery of blood classification material to be hampered.